RegA Plays a Key Role in Oxygen-Dependent Establishment of Persistence and in Isocitrate Lyase Activity, a Critical Determinant of In vivo Brucella suis Pathogenicity - Abdou, Elias; Jiménez de Bagüés, María P.; Martínez-Abadía, Ignacio; Ouahrani-Bettache, Safia; Pantesco, Véronique; Occhialini, Alessandra; Al Dahouk, Sascha; Köhler, Stephan; Jubier-Maurin, Véronique (Frontiers in Cellular and Infection Microbiology, 2017)
For aerobic human pathogens, adaptation to hypoxia is a critical factor for the establishment of persistent infections, as oxygen availability is low inside the host. The two-component system RegB/A of Brucella suis plays a central role in the control of respiratory systems adapted to oxygen deficiency, and in persistence in vivo. Using an original "in vitro model of persistence" consisting in gradual oxygen depletion, we compared transcriptomes and proteomes of wild-type and ∆regA strains to identify the RegA-regulon potentially involved in the set-up of persistence. Consecutive to oxygen consumption resulting in growth arrest, 12 % of the genes in B. suis were potentially controlled directly or indirectly by RegA, among which numerous transcriptional regulators were up-regulated. In contrast, genes or proteins involved in envelope biogenesis and in cellular division were repressed, suggesting a possible role for RegA in the set-up of a non-proliferative persistence state. Importantly, the greatest number of the RegA-repressed genes and proteins, including aceA encoding the functional IsoCitrate Lyase (ICL), were involved in energy production. A potential consequence of this RegA impact may be the slowing-down of the central metabolism as B. suis progressively enters into persistence. Moreover, ICL is an essential determinant of pathogenesis and long-term interactions with the host, as demonstrated by the strict dependence of B. suis on ICL activity for multiplication and persistence during in vivo infection. RegA regulates gene or protein expression of all functional groups, which is why RegA is a key regulator of B. suis in adaptation to oxygen depletion. This function may contribute to the constraint of bacterial growth, typical of chronic infection. Oxygen-dependent activation of two-component systems that control persistence regulons, shared by several aerobic human pathogens, has not been studied in Brucella sp. before. This work therefore contributes significantly to the unravelling of persistence mechanisms in this important zoonotic pathogen.